2021
DOI: 10.3390/ijms22126633
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptional Immunization Can Modulate Offspring Intrathymic IL-17-Producing γδT Cells with Epigenetic Implications Mediated by microRNAs

Abstract: The mechanisms through which maternal immunization can modulate offspring thymic maturation of lymphocytes are not fully understood. Here, we aimed to evaluate whether maternal OVA-immunization can inhibit the maturation of IL-17-producing γδT cells in offspring thymus, and if this mechanism has epigenetic implications mediated by microRNAs (miRNAs) expression. Wild-type (WT) C57BL/6 females were immunized with OVA in Alum or Alum alone and were mated with normal WT males. Evaluating their offspring thymus at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…To evaluate the effect of AD IgG antibodies on cytokine production by thymic γδT cells using a well-established method [ 48 , 49 , 50 , 51 , 52 , 53 ], we collected human thymus from nonatopic infants who were chosen because their mothers had no allergy history. The culture protocol had previously been developed as an in vitro model to investigate the modulatory effect of purified IgG on murine and human thymic and peripheral cells [ 24 , 25 , 26 , 28 , 30 , 32 , 40 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the effect of AD IgG antibodies on cytokine production by thymic γδT cells using a well-established method [ 48 , 49 , 50 , 51 , 52 , 53 ], we collected human thymus from nonatopic infants who were chosen because their mothers had no allergy history. The culture protocol had previously been developed as an in vitro model to investigate the modulatory effect of purified IgG on murine and human thymic and peripheral cells [ 24 , 25 , 26 , 28 , 30 , 32 , 40 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that miRNA expression is significantly dysregulated in inflammatory disorders, such as AD [ 39 ]. Furthermore, in a murine model of atopic disease, a recent study from our group revealed that the thymic functional modulation of IL-17-producing γδT cells had epigenetic implications, as evidenced by the modulation of miRNAs expression on neonatal thymus [ 40 ].…”
Section: Introductionmentioning
confidence: 99%